Routine use of automated strain analysis and 3D echocardiography provides a more comprehensive assessment of cardiac chambers than conventional 2D echocardiography and is time-saving. (4th February 2022) - Volpato, V; Ciampi, P; Johnson, R; Hipke, K; Tomaselli, M; Oliverio, G; Muraru, D; Lang, RM; Badano, LP
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. In most laboratories three-dimensional echocardiography (3DE) and longitudinal strain (Lstrain) analysis are not part of the routine studies. Although these modalities have been shown to provide additional clinical information and prognostic value compared to conventional two-dimensional echocardiography (2DE), their acquisition and analysis are perceived as being time-consuming. Recently, new automated tools have been developed to perform accurate, fast and reproducible analyses of heart chambers' geometry and function. However, their cost-effectiveness when compared to conventional 2DE remains to be demonstrated. Aim. We designed a prospective, multicenter, observational study aimed to compare the time required for the acquisition and analysis of conventional transthoracic 2DE vs advanced echocardiography (AEcho, i.e. 3DE+ Lstrain) for the assessment of cardiac chambers and myocardial mechanics. Methods. According to current guidelines, 196 consecutive patients referred for clinically indicated echocardiography underwent complete 2DE and Doppler echocardiography. In addition, 3DE datasets of the left atrium (LA), left and right ventricle (LV, RV) were acquired using automated 3DE software package (Heart Model). Acquisition time for both 2DE and 3DE images were recorded. Conventional 2DE analyses of LA (biplane volume), LV (biplane volumes and mass) and RV (both linear dimensions, areas, and longitudinal function) were performed following current guidelines, and the time required for acquisition and analysis was recorded. The time spent for AEcho analysis (both 3DE volumetric analysis and Lstrain of LA, LV and RV) was also recorded. Results. Feasibility of AEcho was 86% (169 patients). The additional time for 3D dataset acquisition over conventional 2DE was 38 ± 0.16 sec. Quantitative analysis of the cardiac chambers by 2DE required an average of 5.55 ± 1.51 min vs 4.25 ± 1.23 min using AEcho (p < 0.001). Total time for both 3D dataset acquisition and AEcho assessment was 5.03 ± 1.28 min vs 5.55 ± 1.51 min of 2DE analysis alone (p < 0.001). Globally, AEcho provided a more comprehensive assessment of heart chambers than 2DE (Table). Moreover, the time spent for 3DE dataset acquisition and AEcho analysis on top of standard 2DE acquisition was significantly shorter compared to the 2DE acquisition and analysis (18:50 ± 4.23 vs 19:42 ± 4.24 min, p < 0.001) (Table). Conclusions. Our data showed that the use of new AEcho automated tools are highly feasible resulting in significant time-savings compared to standard 2DE evaluation, while providing significant additional information.